The Evaluation of Teachers Performance in Terms of Pedagogic Competence and Professional Competence in Unesa Labschool Junior High School - Wahyuningtyas, Endah Putri; Handayaningrum, Warih; Wuryani, Eni (International Journal for Educational and Vocational Studies, 2020)
This study was conducted to find out the description of the evaluation of the performance of Unesa Labschool Junior High School Kawung teachers in terms of pedagogical and professional competencies. The method used is qualitative research because it aims to obtain in-depth data and information, so that the goal of knowing and evaluating teacher performance can be achieved. This type of research is an evaluative research, that is, research to look for gaps between real conditions and expectations as determined by existing standards.Subjects in this study were the principal, teachers and students of Unesa Labschool Junior High School Kawung.This study was conducted in the odd semester of the 2019-2020 school year. Data collection techniques used observation, interviews, and documents. The data analysis technique used in this study was an interactive analysis model consisting of three components, namely data reduction, triangulation, data presentation and conclusion making. The results of this study indicate that teacher performance viewed from pedagogical competencies has generally run well and accorded to the academic qualifications and teachers competency standards set by the government. However, the weaknesses of teachers that are still very visible are in creativity in the application of learning both methods and strategies, or in making learning media to support teaching and learning activities. Furthermore, the use of technology is still low and most teachers still use conventional methods in teaching. Whereas teacher performance in terms of professional competence is still not in accordance with academic qualification standards and teacher competencies set by the government. There are still weaknesses in the development of creativity related to media or teaching aids that support learning. In addition, the low implementation of Classroom Action Research (CAR) serves to improve the professionalism of teachers themselves. And the last is the utilization of information and communication technology for personal development that has not been maximized.